The Market, Mind and Rationality. From Vienna to Paris and Back - Rotstein, Abraham (Revue européenne des sciences sociales, 2006)
The mention of the great city of Vienna conjures up the many legacies of music, art and philosophy which it nurtured. But as important as any of these is the more prosaic legacy of the Austrian economists ranging from C. Menger to F. von Hayek. And for some, Vienna may conjure up as well, the debate that K. Polanyi had with these economists in the 1920s. However paradoxical it may seem, it was by virtue of this debate, carried on directly and indirectly over a lifetime, that Polanyi was first and foremost an Austrian, or rather an Austrian «in mirror image ». This was true not only by virtue of the years of his life and his work in Vienna, but more so because he was drawn into and remained a protagonist in the debate around the fundamental issues first raised by the Austrian economists. Menger and his followers E. von Bohm-Bawerk, and L. von Mises had established and diligently pursued much of the agenda of the debate. F. von Hayek was the important representative of this school in recent decades. The particular topic launched by von Mises in 1920 was whether a socialist economy was at all viable without the direction provided by market prices. Regulated or administered prices were bound to lead to economic confusion and the misallocation of resources he maintained.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; MISES, Ludwig von; history of economic thought; regulation; socialist economy

Innis and Polanyi: The Search for the Substantive Economy - Rotstein, Abraham (Journal of Economic Issues; Abingdon, 2014)
Economics and the economy have an uneasy relationship. Economics is akin to the logic of mathematics in contrast to the term "economy," which is an institutional framework to provide for material wants. While they overlap in the modern market economy, economics provides distorted results when applied to tribal societies, the economies of antiquity, or modern state-organized economies. Harold A. Innis and Karl Polanyi both attempted to find a different conceptual framework for a truly general economic history. [PUBLICATION ABSTRACT]
Keywords: INNIS, Harold; business & economics - economic systems and theories; economic history; substantiveness; supply and demand

The reality of society - Rotstein, Abraham (Karl Polanyi and twenty-first-century capitalism, 2020)
In these remarkably stirring reflections, delivered at the 2014 conference from which most of the contributions to this volume emerge, the late Abe Rotstein, Polanyi’s student and collaborator, recalls the projected sequel to The Great Transformation, to be titled Freedom and Technology. Whereas the former was built on a social sciences approach using institutional analysis, the sequel was to follow the intention Hegel expressed in the words ‘Wir die religiöse Vorstellung in Gedanken fassen’ (We want to turn religious expression into philosophical thought). Polanyi took religion seriously – not its outer ceremonial trappings but the important truths that lay behind and beneath these beliefs and practices. The sequel was to trace humanity’s progression through three major revelations: the knowledge of death, the discovery of our inner life and conscience, and the realization of freedom amid our social obligations. This was the idea of ‘the reality of society’ around which the whole book was to be built. It was the precursor of our cherished civil freedoms and closely connected with Polanyi’s idea of freedom in a complex society; it is also deeply threatened in an age of state and corporate cyber surveillance.
Keywords: freedom; reality of society; technology